The occurrence of Nematoda in coastal sea ice on Svalbard (European Arctic) determined with the 18S small subunit rRNA gene - Pitusi, Vanessa; Søreide, Janne; Hassett, Brandon; Marquardt, Miriam; Andreasen, Magnus Heide (Polar Biology, 2021)
Understanding the diversity and functioning of Arctic sea ice ecosystems is vital to evaluate and predict the impact of current and future climate change. In the microscopic communities inhabiting the brine channels inside sea ice, nematodes often dominate numerically and act as bacterivores and herbivores. Despite nematodes great abundances and known ecological roles, molecular tools have not been applied to investigate their species diversity in sea ice. In an attempt to begin establishing a molecular baseline for species diversity of sea ice nematodes, we Sanger sequenced 74 specimens from four locations around Svalbard (European Arctic), using the 18S rRNA barcode. Currently available nucleotide reference databases are both underpopulated with representative marine nematode taxa and contain a substantial number of misidentified organisms. Together, these limitations inhibited the ability to identify marine specimens collected in this study with certainty. Nevertheless, our molecular data indicate the presence of two genera in sea ice on Svalbard—Theristus and Halomonhystera. While it is possible that the latter represents a novel ice nematode species, future studies, including morphometric analysis, are needed to verify our molecular findings. We leverage the assignment of molecular information to robustly identify nematodes and provide the first insight into the diversity of sea ice nematodes in the European Arctic. We advocate for an intensified cooperation between molecular and morphological taxonomists to expedite the establishment of baseline surveys that are required to predict biological consequences of the diminishing sea ice habitat in the future.